The Third Sector as a Renewable Resource for Europe Concepts, Impacts, Challenges and Opportunities - Enjolras, Bernard (Springer Nature, 2018)
Third sector impact; Volunteering; Charity; European Commission; Political legitimacy; Third Sector in Europe; Third Sector as a Renewable Resource; Obstacles to Third Sector Organisation; Development in Europe